A sensitive colorimetric hydrogen sulfide detection approach based on copper-metal–organic frameworks and a smartphone. Issue 12 (8th March 2022) - Hong, Chengyi; Li, Dandan; Wang, Ziyue; Liu, Boyuan; Zhang, Wenmin; Zhang, Kailong; Huang, Zhiyong
Abstract : A colorimetric approach is developed for the detection of hydrogen sulfide (H2 S) in water samples based on copper-metal–organic frameworks (Cu-MOFs) and a smartphone. Abstract : In this study, we demonstrate a colorimetric approach for the detection of hydrogen sulfide (H2 S) in water samples with high sensitivity. Firstly, copper-metal–organic frameworks (Cu-MOFs) were synthesized by ultrasonic-assisted hydrothermal method, presenting a maximum absorption peak at 700 nm. It was found that Cu-MOFs could react with H2 S to form a copper–sulfur complex along with a decrease of the absorption peak at 700 nm and a visible color change from blue to tan. Under the optimal reaction conditions, the absorption intensity at 700 nm was linear with H2 S concentration in a range of 0.05–2 mM ( R 2 = 0.9928), providing a detection limit of 22 μM. Furthermore, the method was successfully applied to the detection of H2 S in lake water samples with a recovery rate between 94.4% and 112.6%. In addition, a practical and portable device for on-site H2 S detection was designed by using agarose hydrogels, and a simple colorimetric detection method based on a smartphone was developed. This analytical method showed good selectivity for H2 S compared to other interfering substances, and the feasibility of the agarose hydrogel-based device was proved by the determination of H2 S in real lake water samples.